Implementasi Pendekatan Ekonomi Manajerial Berbasis Keislaman dalam Pengembangan Kinerja Bisnis - Imsar, Imsar; Harahap, Alfi Ardiansyah (Hikmah, 2023)
The ebb and flow of a business is highly dependent on the capital and strategies used. However, existing capital and strategies will not necessarily succeed when business management is not well organized. Not a few of the entrepreneurs only focus on capital, but forget the managerial approach. With regard to that, this study aims to analyze the implementation of an Islamic-based managerial approach in developing the performance of the chocolate ice business. This research uses a case study-based qualitative research method. Data collection uses observation, interviews, and documentation studies. The results showed that the implementation of an Islamic-based managerial economic approach is carried out by bringing together an understanding of economic theory with decision-making skills that can be applied to conduct analysis and make profitable decisions for the company. It acts as an accurate analysis and decision-making tool to support the company's progress. In its implementation, there are seven aspects of concern, namely cost-benefit analysis, rational decision making, efficient resource management, budget planning and control, performance evaluation, risk management, investment decision making. in addition, the islamic principle, namely compliance with the principles of business in islam, is an important thing that underlies the managerial economic approach.